Bacteria--phagocyte dynamics,axiomatic modelling and mass-action kinetics - Roy Malka; Vered Rom-Kedar (Mathematical Biosciences and Engineering)
Axiomatic modeling is ensued to provide a family of models that describe bacterial growth in the presence of phagocytes, or, more generally, prey dynamics in a large spatially homogenous eco-system. A classification of the possible bifurcation diagrams that arise in such models is presented. It is shown that other commonly used models that do not belong to this class may miss important features that are associated with the limited growth curve of thebacteria (prey) and the saturationassociated with the phagocytosis (predator kill) term. Notably, these features appear at relatively low concentrations, much below the saturation range. Finally, combining this model with a model of neutrophildynamics in the blood after chemotherapy treatments we obtain new insights regarding the development of infections under neutropenic conditions.